2021
DOI: 10.1097/mph.0000000000002376
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in Methods and Timing for Delivery of Genetic Counseling Information to Pediatric Oncology Patients and Families

Abstract: Many pediatric oncology patients and their families may benefit from genetic counseling and testing; however, identifying the best timing and delivery method for these referrals is sometimes a challenge. The goal of this study was to understand how and when caregivers prefer to receive information about genetic counseling and testing. A total of 56 surveys completed by caregivers at The Johns Hopkins Hospital Pediatric Oncology unit in Baltimore, Maryland were analyzed. A sizeable subset of respondents was int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In a recent study looking at appropriate timing for genetic counseling information, families indicated they would like to be informed about this information at diagnosis or within 1 to 2 months of the diagnosis. 8 Our study was able to collect information regarding the time it took for a participant to be seen in the CPP after their diagnosis. There were 21 participants who had a genetic evaluation within 2 months of their diagnosis (77.8%) and 6 participants with an evaluation > 2 months (22.2%).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study looking at appropriate timing for genetic counseling information, families indicated they would like to be informed about this information at diagnosis or within 1 to 2 months of the diagnosis. 8 Our study was able to collect information regarding the time it took for a participant to be seen in the CPP after their diagnosis. There were 21 participants who had a genetic evaluation within 2 months of their diagnosis (77.8%) and 6 participants with an evaluation > 2 months (22.2%).…”
Section: Discussionmentioning
confidence: 99%